Precautionary measures of personal character, general power of caution and mitigated category list - Pedro Machado de Almeida Castro (Revista Brasileira de Direito Processual Penal, 2017)
This is a study that aims to point the possibility of adopting an intermediate vision between the extreme positions of application of personal precautionary measures in the criminal procedural law, namely, the general power of caution vs. closed list of applicable measures. Thus, it is not intended to analyze requirements and forms of application of personal precautionary measures, but only whether or not there is a liberality of creation and application of these measures, provided by law or not, by the magistrate.